Nasal polyp syndrome: a patient-centred term for CRSwNP by EUFOREA - Teeling, T.; Djouder, C.; Laurens, H.; Preyra, J. H.; Shire, C. M. E.; Van Staeyen, E.; Conti, D. M.; Scadding, G. K.; Hellings, P. W. (Frontiers in Allergy, 2024)
Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) is a chronic inflammatory disease of the nose and paranasal sinus cavities that significantly affects well-being and social function, particularly in young adults and middle-aged populations. CRSwNP is a common health condition in the Western world, with an estimated prevalence of 3%. Despite worldwide evidence-based treatment guidelines such as the European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS) 2020 and the European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) chronic rhinosinusitis (CRS) pocket guide, a significant number of patients remain undiagnosed and/or uncontrolled with repeated oral corticosteroids (OCS) treatments and/or (multiple) endoscopic sinus surgeries (ESS).